Transmission of pathogenic fungi from seeds to seedlings in cotton (Gossypium hirsutum L.) (Dhaka University Journal of Biological Sciences, 2023)
Cotton seeds of susceptible variety CB10 were inoculated with nine pathogenic fungi viz., Aspergillus flavus, A. niger, A. tamarii, Colletotrichum gloeosporioides, Curvularia lunata, Fusarium nivale, F. moniliforme, Mucor sp. and Rhizoctonia solani. Seedlings were grown in water agar test tube and in earthen pots. In water agar test, R. solani showed the highest percentage of seed to seedling transmission (35.27%) which was followed by F. moniliforme (31.29%) and A. niger showed the lowest (8.03%) transmission. Germination percentage of control seeds was 90.32% whereas in pathogen inoculated seeds it varied from 58.33 to 89.07%. The seedling mortality percentage was highest in R. solani (46.68%) and lowest in C. gloeosporioides (18.67%). Germination percentage of control seeds in pot was 99% whereas in pathogen inoculated seeds it varied from 43.37 to 84.34%. The seedling mortality percentage was highest in F. moniliforme (48.28%) and lowest in A. niger (19.64%). Percentage of seed to seedling transmission of fungi varied from 17.85% (A. niger) to 46.56% (F. moniliforme).Dhaka Univ. J. Biol. Sci. 32(2): 225-232, 2023 (July)